2012
DOI: 10.1016/j.apenergy.2011.12.088
|View full text |Cite
|
Sign up to set email alerts
|

Domestic hot water consumption vs. solar thermal energy storage: The optimum size of the storage tank

Abstract: Many efforts have been made in order to adequate the production of a solar thermal collector field to the consumption of domestic hot water of the inhabitants of a building. In that sense, much has been achieved in different domains: research agencies, government policies and manufacturers. However, most of the design rules of the solar plants are based on steady state models, whereas solar irradiance, consumption and thermal accumulation are inherently transient processes. As a result of this lack of physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(39 citation statements)
references
References 38 publications
0
38
0
Order By: Relevance
“…Annual average domestic hot water (DHW) energy consumption per house in different regions from Spain [3]. Recent research made by Rodriguez-Hidalgo [4] shows that DHW consumption depends not only on the geographical situation, but also on people's habits, the time of year, and the purpose of the building. Differences shown in Table 2 could be caused by inlet temperature of cold water or other parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Annual average domestic hot water (DHW) energy consumption per house in different regions from Spain [3]. Recent research made by Rodriguez-Hidalgo [4] shows that DHW consumption depends not only on the geographical situation, but also on people's habits, the time of year, and the purpose of the building. Differences shown in Table 2 could be caused by inlet temperature of cold water or other parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Several different estimates are found in the literature. For example, Rodriguez-Hidalgo et al (2012) have reported on a study of the hot water use of 215 inhabitants. The average water draw for each hour is shown in Figure 10.…”
Section: Simulation Of Sdwh System Performancementioning
confidence: 99%
“…Hot water consumption further depends on people's habits, the time of the year, the building type, the building usage and also on the inhabitants' specific lifestyle, etc. [40]. However, such dependencies can vary spatially, as well as temporally, or they tend to cluster in space and time.…”
Section: Figurementioning
confidence: 99%